AN ANALYSIS OF GRICE'S COOPERATIVE PRINCIPLE IN ROSÉ’S YOUTUBE INTERVIEW: A PRAGMATIC APPROACH - Andra, Meidi; Afriana, Afriana (BASIS (Bahasa dan Sastra Inggris), 2025)
This study investigates the application of Grice’s Cooperative Principle in spoken discourse by analyzing Rosé’s utterances during her interview on the i-D YouTube channel. Employing a descriptive qualitative approach, the research identifies how the four conversational maxims—quantity, quality, relation, and manner—are manifested in her responses. The data are obtained through non-participatory observation and note-taking and analyzed using a pragmatic identity method. A total of 22 utterances were identified, with the maxims of quantity and relation (36.36%) being the most frequently observed. The findings show that Rosé’s responses largely adhered to the principles of quantity and relevance, reflecting a cooperative communication style. These findings highlight a growing trend in pragmatic research: the context-dependent application of Grice’s maxims in public discourse. Despite these developments, there remains a notable gap in research focusing specifically on K-pop artist interviews within digital platforms such as YouTube. Considering this, the present study contributes to a broader understanding of cooperative communication in media discourse and offers insights into the continued applicability of Gricean theory in analyzing contemporary public interactions.